Genetic diversity in several genotypes of Algerian lentil using biochemical markers - Hamida Hammadi; DOUNIA HAMMOUDA-BOUSBIA; GHANIA CHAIB; ANFEL TIR (Society for Indonesian Biodiversity, 2021)
Abstract. Hammadi H, Hammouda-Bousbia D, Chaib G, Tir A. 2021. Genetic diversity in several genotypes of Algerian lentil using biochemical markers. Biodiversitas 22: 3494-2500. Studying seed storage proteins in legumes (Fabaceae) is very important besides its economic value; seed storage proteins play an important role in plant taxonomy because of the stability of their contents. The grain protein content and protein profiles of 12 lentil genotypes (Lens culinaris Medik.) were characterized based on protein profiling through SDS-PAGE. The obtained gel has shown forty bands ranged from 13 to 21 with molecular weight 10 to 120 KDa. Of which six monomorphic bands, thirty-four polymorphic bands and five unique bands in Flip90-31, Idlep3, idlep2, Idlep4 and Radjas genotypes. The protein banding pattern polymorphism (84%) revealed an inter-genotypic variability. The Idlep3 genotype is characterized by specific bands (or a specific marker), followed by the Flip90-31 genotype. So these two genotypes can be considered as valuable gene resources for further breeding programs.